P‐127: Pixel Aliasing Methods for Voxel Resolution Enhancement of Multiview Display - Son, Wonseok; Kim, Youngrok; Min, Sung‐Wook (SID International Symposium Digest of technical papers, 2024)
Pixel aliasing method is proposed to increase the resolution of multiview 3D display. where the deterioration of 3D image resolution occurs due to producing multiple directional images with limited display resolution. To overcome the resolution limitations of discrete voxels, we rearrange the image pixels by using the resizing technique and the interpolation method to enhance the 3D image resolution. We demonstrate the image resolution increase in both the depth and horizontal directions.